Evaluation of thermodynamic data and phase equilibria in the system Ca–Cr–Cu–Fe–Mg–Mn–S part I: Binary and quasi-binary subsystems. (March 2017) - Jantzen, Tatjana; Hack, Klaus; Yazhenskikh, Elena; Müller, Michael
Abstract: The Ca–Cr–Cu–Fe–Mg–Mn–S system has been thermodynamically assessed using all available experimental data. The thermodynamic description of the high-temperature phase Chromium and Iron Pyrrhotite is described using a two-sublattice model which allows the description of the stability range of this phase in the binary Fe–S and Cr–S systems and also the solubility of such elements as Cu, Mg and Mn in the binary systems. Particular attention was given also to the phases Oldhamite and Digenite, which exhibit very wide solubility with respect to the metal elements. In this part of the report binary and quasi-binary subsystems are presented. Highlights: Ca–Cr–Cu–Fe–Mg–Mn–S system thermodynamically assessed. Binary Me–S and quasi-binary systems Me1 S-Me2 S considered here. Modified associate species model used for the liquid phase. 6 solid solutions introduced using the multi-sublattice approach. Calculated phase diagrams and thermodynamic properties in good agreement with the experimental data.